PENDAMPINGAN PEMBELAJARAN MATEMATIKA MATERI OPERASI PERKALIAN BAGI SISWA SD KELAS II SDN 42 PALEMBANG - Lisnani, Lisnani; Setiawan, Adrianus Danang; Stevani, Afiliani Likurnia; Septian, Albertus Ivan (Jurnal Terapan Abdimas, 2020)
Abstract. Community service carried out by the dedication team consisted of lecturers and students of the Musi Charitas Catholic Primary School Teacher Education Study Program in cooperation with Elementary School State No.42. Community service is carried out in five meetings with a duration of two hours per meeting. Each meeting, the dedication team uses a summary of the material and questions about multiplication operations. The assistance provided by the service team outside of school hours is in the form of additional hours and is prioritized for children with low and moderate abilities. The method used is the lecture method, discussion, question and answer, and discovery learning models. In addition, this assistance process is carried out where one person accompanies a maximum of three students with the aim of getting maximum results. Output generated in this service activity is a summary of material and questions about multiplication counting operations. The summary of the material and questions provided aims to train students' abilities to more easily understand the overall multiplication operation.Abstrak. Pengabdian kepada masyarakat yang dilaksanakan oleh tim pengabdian terdiri dari dosen dan mahasiswa Program Studi Pendidikan Guru Sekolah Dasar Universitas Katolik Musi Charitas bekerjasama dengan SD Negeri 42 Palembang. Pengabdian kepada masyarakat yang dilakukan sebanyak 5 kali pertemuan dengan durasi 2 jam tiap pertemuan. Tiap pertemuan, tim pengabdian menggunakan ringkasan materi dan soal tentang operasi perkalian. Pendampingan yang dilakukan oleh tim pengabdian di luar jam sekolah berupa jam tambahan dan diutamakan bagi anak-anak yang berkemampuan rendah dan sedang. Metode yang digunakan ada metode ceramah, diskusi, tanya jawab, dan model pembelajaran discovery. Di samping itu, di dalam proses pendampingan ini dilakukan dimana 1 orang mendampingi maksimal 3 siswa dengan tujuan untuk mendapatkan hasil yang maksimal. Luaran yang dihasilkan dalam kegiatan pengabdian ini berupa ringkasan materi dan soal tentang operasi hitung perkalian. Ringkasan materi dan soal yang diberikan bertujuan untuk melatih kemampuan siswa agar lebih mudah memahami operasi perkalian secara keseluruhan.